Rapid and reliable identification of insulin 2 gene mutation in Akita diabetic mice by a tetra-primer-ARMS-PCR method - Rambabu Undi; Hui-Ying Lim; Weidong Wang (Heliyon, 2019)
The Akita mouse, one of the most frequently used animal models for the study of diabetes mellitus and its complications, carries a heterozygous missense mutation (C96Y) in the insulin 2 (Ins2) gene that results in proinsulin misfolding in the endoplasmic reticulum (ER), ER stress, pancreatic beta cell death and ultimately diabetes. Maintenance of Akita mice entails genotyping for the identification of the heterozygous Akita mutation. Current genotyping methods for the Akita mouse strain are time consuming, expensive, or needing special device. Here, we develop a simple, fast, cost-effective, and reliable genotyping methodology for the Akita mice. Utilizing the tetra-primer amplification-refractory mutation system polymerase chain reaction (ARMS-PCR) with primers that are specific for normal alleles or Akita mutant alleles, we obtained amplified PCR products that allowed us to distinguish between the wild-type (+/+), heterozygous (Ins2Akita/+), and homozygous (Ins2Akita/Ins2Akita) mice within 3 hours. These results present the ARMS-PCR analysis as highly desirable and suitable for the identification of the Akita mutation, which is expected to significantly facilitate and promote the Akita mouse-related studies.